A holistic review on optimization strategies for combined economic emission dispatch problem. (January 2018) - Mahdi, Fahad Parvez; Vasant, Pandian; Kallimani, Vish; Watada, Junzo; Fai, Patrick Yeoh Siew; Abdullah-Al-Wadud, M.
Abstract: Power generation system largely depends on fossil fuels to generate electricity. Due to various reasons, the reserves of fossil fuels aredeclining and will become too expensive in near future. At the same time, generation of power from fossil fuels causes hazardous gases and particulates to emit, which pollutes the air and causes significant and long termdamages onthe environment. For this reason, extensive research works have been conducted for last few decades from different perspectives to reduceboth the fuel cost aswell as the emission of hazardous gasesin power generation system. This power generation problem is commonly referred to as the combined economic emission dispatch (CEED) problem. This paper provides a comprehensive reviewon the uses of different optimization techniques to solveCEED problem. Authors have found advanced nature-inspired methods as the most suitable and successful, and have concluded combinational hybrid methods as the most prospective methods to solveCEED problem.